COVID-19, and Vitamin D, and Air Pollution Global Epidemics Impact on Older Adults - Ray Marks (Journal of Aging Research And Healthcare, 2020)
Background Most current Corona virus or COVID-19 pandemic deaths have been found to occur among populations older than 65 years of age, who often suffer from the presence of an array of chronic diseases that may be related to a co-occurring vitamin D deficiency. Another factor affecting older adults’ immune response mechanisms is air quality. In turn, air quality can impact the absorption of vitamin D from sunlight sources, a factor which could explain why older people, who are often vitamin D deficient, may be more likely than younger adults or healthy adults to be at risk for COVID-19 and poor outcomes. Aim This work was designed to examine the recent literature on COVID-19, vitamin D and air pollution and what it might imply for public health workers, policy makers, and others. Methods Available data accessed largely from the PUBMED data base for the year 2020 using the key words COVID-19, air pollution, and vitamin D deficiency were sought and selected items were carefully examined and documented in narrative and tabular formats. Results Many publications on COVID-19 prevail, but far fewer focus specifically on vitamin D deficiency and its possible role in explaining COVID-19 global health risk among older adults. A similar, albeit small number of publications, discuss the global pandemics of air pollution and its possible COVID-19 association, as well as its impact on vitamin D production. However, while most related articles support a possible independent as well as a dual role for both factors in COVID-19 the realm of this highly infectious widespread disease, very few actual studies have been conducted to date on any of these topical issues Conclusion More research to examine if vitamin D-based nutrients or supplements may provide some degree of community wide protection against COVID-19 in the older vitamin D populations, especially among those living in highly polluted areas may prove highly valuable. Controlling air pollution emissions globally and locally may also prove to be a highly impactful public health approach to reducing overall COVID-19 risk, and extent, and warrants study.
Keywords: COVID-19